Baclofen as a therapeutic option for gastroesophageal reflux disease: A systematic review of clinical trials - Arabpour, Erfan; Khoshdel, Sina; Akhgarzad, Ali; Abdi, Mohammadamin; Tabatabaie, Negin; Alijanzadeh, Dorsa; Abdehagh, Mohammad (Frontiers in Medicine, 2023)
Background: The main components of gastroesophageal reflux disease (GERD) management include a combination of medications and lifestyle modifications; Nevertheless, based on the severity of symptoms and their response to medications, other treatments could be considered. Baclofen has been demonstrated in studies to relieve GERD symptoms. The current study aimed to precisely address the effects of baclofen on the treatment of GERD and its characteristics. Methods: A systematic search was carried out in Pubmed/Medline, Cochrane CENTRAL, Scopus, Google Scholar, Web of Science, and clinicaltrials.gov up to December 10, 2021. The search terms included baclofen, GABA agonists, GERD, and reflux. Results: We selected 26 papers that matched the inclusion criteria after examining 727 records. Studies were classified into four categories based on the study population and reported outcomes:1) adults 2) children 3) patients with gastroesophageal reflux-induced chronic cough 4) Hiatal hernia patients. The results revealed that baclofen can significantly improve reflux symptoms and pH-monitoring and manometry findings to different degrees in all four mentioned categories; although its effect on pH-monitoring parameters seems less significant than the other parameters. Mild neurological and mental status deterioration were the most reported side effects. However, side effects occurred in a portion of less than 5% of short-term users and nearly 20% of long-term users. Conclusions: In PPI-resistant patients, a trial of adding baclofen to the PPI may be helpful. Baclofen therapies may be more beneficial for symptomatic GERD patients who also report concurrent conditions including alcohol use disorder, non-acid reflux, or obesity. Keywords: Baclofen, GABA agonist, Gastroesophageal reflux disease, Reflux, GERD